Consumer Protection for Traffic Accident Victims Due to a collision with an online motorcycle taxi that violates - Kusuma, Rizky; Ferdiles, Lucky; Darwati, Darwati (Blantika: Multidisciplinary Journal, 2024)
In the era of globalization, the number of private vehicles is increasingly two-wheeled. Hit-and-run traffic violations in Gelora Karno, Central Jakarta Polrestabes area between scooters against and private motorcycles and traffic accidents between online motorcycle taxis that go against the flow and private motorcycles. This study aims to determine consumer safety standards against traffic accidents caused by online motorcycle taxi drivers. The legal research method that the author uses is empirical juridical, the method is carried out by examining the law or from facts that are actually obtained from the field in the form of information, characteristics and effectiveness. The results of the study concluded that Law Number 8 of 1999 concerning Consumer Protection and Law Number 22 of 2009 concerning Road Traffic and Transportation are regulations that regulate motorists when driving on the highway, through consumer protection efforts and driver legal responsibility designed to reduce the number of traffic violations by conducting frequent socialization and routine patrols every day in the field. The driver is liable based on the category of misdemeanor, moderate or severe against applicable law. Consumer protection is given to victims so that they do not experience trauma and are healthy again.